Development of Possible Solution to Overcome Factors Influence on Sustainable Construction Process - Hazem, Ryad Tuma; Breesam, Hatem Khaleefah (Civil Engineering Journal, 2019)
The both of time challenges and technology developments are having influence on changes in the required level of any types of industries and in any country in the world. The importance of construction industry is making this sector need to develop without forgetting the negative impacts of the construction process on environment aspects. The objective of this paper is to identify the factors within negative impacts on sustainable process in construction industries by taking the vision of specialists via questionnaire techniques.Â  The Identified factors has been divided into three groups each group associated with the concepts of integrated sustainable. The study is focused on â€œrequired actionsâ€ that have been drawn through experts to show the roadmap that will help the contractual parties to start in converting the traditional process on construction to be sustainable process. Through the conclusions can be reached facts that contribute to the adoption of sustainable standards in the construction industry in Iraq as a developing country.